O niektórych animizacjach i personifikacjach w twórczości Stefana Żeromskiego - Handke, Kwiryna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
Stefan Żeromski was a writer and a person with very strong ties with nature. He was especially close to the world of fauna and flora, which he knew and observed well. Żeromski largely introduced this outside world into his writings. In his representations, the author made use of different linguistic and stylistic means such as: names and designations, appositional conjunctions, periphrases, hyperboles and other, and primarily metaphors and comparisons including animization and personification. Żeromski made use of animization as a form of an extended metaphor or a comparison, mainly with reference to floral objects, to which he attributed various human characteristics— the appearance and actions, human behaviours and sensual feelings, and even the means of communication with the environment. In the texts of Żeromski, personification—as a more complete form of animization— includes plants, and, from the animal realm, mainly birds, often assuming the form of short stories. The questions presented in the article have been illustrated with extended quotations from the diaries of the writer as well as from various fabular writings of his authorship.